A Serum Component Related to Nonimmunoglobulin Amyloid Protein AS, a Possible Precursor of the Fibrils - Husby, G. (1974)
A nonimmunoglobulin protein with the molecular weight of 9,145 (protein AS) has been shown to be a principal component of the amyloid fibrils in different clinical types of amyloidosis. A protein component, antigenically closely related to protein AS, was detected in human sera. The protein AS-related component (protein ASC) was found in the sera of many groups of patients, including 48 out of 55 patients with various clinical types of amyloidosis. No structural relationship of protein ASC to the plasma component of amyloid was found. Protein ASC was also present with high frequency in the serum of diseases known to be frequently complicated by amyloidosis. In some cases, ASC was found in the sera of patients 2-3 yr before the diagnosis of amyloidosis was established. Protein ASC was also frequently found in hypogammaglobulinemia. Among normal individuals, protein ASC was seldom detected in the serum by our techniques, but there was a noticeable increase with age and during pregnancy. Moreover, a more sensitive technique, immunoelectro-osmophoresis, revealed protein ASC in a higher number of sera from both patients and normal controls. Thus protein ASC was suggested to be a normal serum constituent, usually present only in minor quantities. Under certain conditions, protein ASC increases considerably in serum, and may in such instances act as a precursor for the deposition of amyloid fibrils in the tissues.